Inflammasome-Dependent Coagulation Activation in Sepsis - Wu, Runliu; Wang, Nian; Comish, Paul B.; Tang, Daolin; Kang, Rui (Frontiers in Immunology, 2021)
Sepsis is a potentially life-threatening, pathological condition caused by a dysregulated host response to infection. Pathologically, systemic inflammation can initiate coagulation activation, leading to organ dysfunction, and ultimately to multiple organ failure and septic death. The inflammasomes are cytosolic multiprotein signaling complexes that control the host response to diverse pathogen-associated molecular patterns (PAMPs) from microorganisms as well as damage-associated molecular patterns (DAMPs) from dead or dying host cells. Recent studies highlight that the activation of canonical and non-canonical inflammasomes not only mediate the maturation and secretion of interleukin-1 (IL1) family cytokines, but also trigger the release of coagulation factor III, tissue factor (F3, best known as TF) in activated macrophages and monocytes. These emerging functions of inflammasomes in immunocoagulation are further positively regulated by stimulator of interferon response cGAMP interactor 1 (STING1, also known as STING or TMEM173, a hub of the innate immune signaling network) and high mobility group box 1 (HMGB1, a nuclear DAMP). This mini-review will discuss the regulation and function of inflammasome-dependent coagulation activation in sepsis.